The utilization of Sentinel-1 and intermittent SBAS DInSAR for enhanced deformation monitoring of geohazards - Gee, David C. (2021)
The monitoring of land motion can provide critical information on potential geological hazards. Geohazards are phenomena that can pose significant socio-economic and environmental risks. There have been an increasing number of geohazard mapping programmes across the world that utilise space-related technologies, such as the Global Navigation Satellite System (GNSS) and Earth Observation (EO). Differential interferometric synthetic aperture radar (DInSAR) is an EO technique that utilizes spacebourne synthetic aperture radar (SAR) data to measure millimetric rates of ground deformation from the differences in phase between image acquisitions. However, two significant limitations of DInSAR analysis are that incoherence restricts measurements to urbanised or rocky areas and free, readily available data with sufficient temporal coverage has not historically been available. In this regard, the Intermittent Small Baseline Subset (ISBAS) is a processing algorithm which is capable of computing velocities over land cover types that have typically been unfavourable for DInSAR analysis. In addition, as part of the Copernicus EO program, the Sentinel-1 satellite provides readily available conflict-free data every 6 days in Europe. The purpose of this research is to demonstrate the potential of the ISBAS processing method and Sentinel-1 SAR data for enhanced capability to monitor ground movements related to geological hazards. Previously, the initial results utilizing the ISBAS method on archive data have identified notable deformations over former coalfields in the UK. Here, previous research was revisited over the Northumberland and Durham coalfield, whereby the ISBAS method was applied to archive and Sentinel-1 data providing deformation data spanning 3 decades. The results show that unexpected and changing amounts of ground motion can be present over former coalfields. The near complete coverage of measurements aided the interpretation and most notably temporal correlations between the rise of mine water and surface heave were made. The results showed that ISBAS measurements had the potential to be utilized to map changes in groundwater levels. Subsequently, an analytical model based upon the principle of effective stress and concept of mine water ponds was developed to relate changes in groundwater levels to changes in the thickness of the strata and, hence, determine surface movement. The forward models estimate surface heave utilising measurements from monitoring boreholes. The models were calibrated and validated using ISBAS measurements, where good agreement was found between the model and the DInSAR, over the demonstration site of the Nottinghamshire coalfields. The ISBAS measurements were then inverted to estimate the change in groundwater levels across the whole coalfield, providing greater spatial coverage than could be inferred from the spatially sparse monitoring boreholes or the forward model. The inverse map was then utilized to predict the time it will take for groundwater to discharge out of the Coal Measures rock. Additionally, the seamless coverage and regular revisit of Sentinel-1 affords the potential for wide-area monitoring of mining deformations and other geohazards. This was demonstrated over the Netherlands where multiple stacks of data were processed and mosaicked together to produce a wide-area-map. The motions, attributed to compressible soils, infrastructure settlement, peat oxidation, gas production, salt mining and underground and opencast mining, were validated with all available independent ancillary information such as previous persistent scatterer interferometry (PSI) deformation maps, models of subsidence and settlement susceptibility and GPS measurements. A statistical analysis showed that measurements in rural areas can provide reliable information with a high degree of confidence (5σ). Finally, the processing requirements for a full Europe-wide deformation map were calculated to determine the opportunity and challenges Sentinel-1 presents for future operational services.